Engagement on Student’s Academic Presentation - Aisyah Ririn Perwikasih Utari; Januarius Mujiyanto; Suwandi Suwandi; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
The basic aim of academic presentations is generally for turning the written ideas into the spoken ones. Most of the ideas presented are in academic or scientific matters. In the university level, the activities of prsentations become ordinary ways to share ideas and discussions, mostly done as the output of course assignments. This is why the skill of presentation is important for students, especially in English. Academic presentation for non-native English speakers will be a little bit hard to do, for some students in English Department as well. They will easily share ideas in Bahasa Indonesia or if it is in English, it is easier to have casual conversation rather than having a presentation in English. Students need this kind of experience. The experience that brings them to engage with audience when they do an academic presentation, even it is inside or outside the classroom, for example an international forum or conference. Choosing the mode that they choose for the presentation is also important to build the audience engagement. It becomes harder when they consider that speaking English during the presentation makes them facing more complicated problems dealing with how to communicate with the audience, both in presentation and question and answer sessions. Forey and Feng (2016) state that engagement is analyzed through four features of engagement in academic presentations: 1) speech signs; 2) involvement; 3) social distance; 4) affect. The features support relevant analysis of engagement visually on the verbal and nonverbal act during the students’ presentation. It practically opens the students’ mind and knowledge about how to achieve the audince’s engagement within their session.